Preparation of nanocrystalline YbFeO3 by sol-gel method and its visible-light photocatalytic activities. (10th December 2017) - Tang, Peisong; Yu, Longlong; Min, Jiayuan; Yang, Jiani; Chen, Haifeng
ABSTRACT: Using Fe(NO3 )3 ·9H2 O, Yb(NO3 )3 ·5H2 O, citric acid and ethylene glycol as main raw materials, the gel of YbFeO3 was prepared by sol-gel method. The gel was kept at 100 °C for 36 h to make xerogel. Then, the xerogel was calcined in muffle furnace at 800°C to make YbFeO3 samples. The structure and morphology of samples were characterized by thermogravimetry and differential scanning calorimetry (TG-DSC), powder X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy and UV-visible diffuse reflectance spectroscopy (DRS). The results showed that the perovskite structure YbFeO3 was obtained through sol-gel method. The resulting products have a particle size of 80 nm and an optical band gap of 2.0 eV. Consequently, the YbFeO3 nanoparticles showed high photocatalytic activities for decomposition of methyl orange under visible-light irradiation.